2019
DOI: 10.1007/s00271-019-00632-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of regulated deficit irrigation during the vegetative growth period on shoot elongation and oil yield components in olive hedgerows (cv. Arbosana) pruned annually on alternate sides in San Juan, Argentina

Abstract: Effect of regulated deficit irrigation during the vegetative growth period on shoot elongation and oil yield components in olive hedgerows (cv. Arbosana) pruned annually on alternate sides in San Juan, Argentina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
3
19
0
1
Order By: Relevance
“…Even under such conditions, vegetative growth may not be optimal due to the high water stress sensitivity of growth to reductions in SWP (Pérez-López et al, 2007). In young orchards, crown development is very important for reaching maximum yields per hectare, but in mature orchards with super high densities, moderate water stress (−1 to −1.2 MPa SWP; Moriana et al, 2012;Gómez del Campo, 2013) could reduce pruning costs and increase yields by reducing shading (Trentacoste et al, 2019). Maintaining SWP near the baseline would be the best strategy during these phenological stages because fruit and oil yield is strongly affected by early water stress (Rapoport et al, 2012).…”
Section: Phase IIImentioning
confidence: 99%
“…Even under such conditions, vegetative growth may not be optimal due to the high water stress sensitivity of growth to reductions in SWP (Pérez-López et al, 2007). In young orchards, crown development is very important for reaching maximum yields per hectare, but in mature orchards with super high densities, moderate water stress (−1 to −1.2 MPa SWP; Moriana et al, 2012;Gómez del Campo, 2013) could reduce pruning costs and increase yields by reducing shading (Trentacoste et al, 2019). Maintaining SWP near the baseline would be the best strategy during these phenological stages because fruit and oil yield is strongly affected by early water stress (Rapoport et al, 2012).…”
Section: Phase IIImentioning
confidence: 99%
“…The system improved its performance after the first year of adjustment. Recent studies have reported that RDI strategies can be advantageous in SHD olive orchards in terms of reducing water applications, decreasing excessive tree vigor, improving irradiance environments and increasing yield, oil quality and water-use efficiency [1,6,[61][62][63]. The results of the present study provide evidence that an RDI strategy can be applied through a DSS in a plot of SHD olive orchards with no negative effects on yield, number of fruits per tree, oil yield, WP yield or WP oil yield, if there is prior spatial characterization and pre-established criteria for decision making.…”
Section: Crop Water Status and Productivitymentioning
confidence: 99%
“…Irrigation is very important in SHD olive groves to ensure high productivity, as the trees have a limited root volume, a high leaf area index and, in consequence, high water demands [4,5]. However, the application of excessive amounts of water can lead to uncontrolled vigor, the need for severe pruning to adapt the hedgerow to the operation of the mechanical harvester, and low lighting in the fruiting areas, producing an imbalance between growth and productivity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Olive fruit growth (expressed as fresh weight) follows a double sigmoid curve [16]. Previous reports have identified two periods during fruit growth that are particularly sensitive to water restriction: an initial one during cell division and the expansion phase, from flowering until the end of fruit set, where deficit irrigation can reduce the final fruit number [15,17]; and a second one, during cell expansion and the lipogenesis phase, after pit hardening until harvest, when fruit growth increases sharply as mesocarp cells expand. A deficit in irrigation during this period can reduce the final fruit weight and oil content, and it can affect the oil composition, such as the polyphenol content [18][19][20].…”
Section: Introductionmentioning
confidence: 99%